UMPSA organized ICCEIB, focuses on the SDG collaborative approach to food, energy, and water security - Naqiah, Puaad (UMPSA, 2024)
PUTRAJAYA, 28 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organized the 7th International Conference on Chemical Engineering & Industrial Biotechnology (ICCEIB) 2024, held from 27 to 29 August 2024, in Putrajaya.